Komunikasi Dan Transformasi Kelembagaan: Studi Peran EX UPK PNPM MDP Dalam Transisimenuju Koperasi Desa Merah Putih - Aziman, Muhammad Fauzan (STAI Bumi Silampari, 2025)
This study examines the institutional transformation of the Program Management Unit (UPK) of the National Rural Community Empowerment Program (PNPM MPd) into the Merah Putih Village Cooperative in Lebong Regency, Bengkulu. Using a qualitative case study approach with 15 key informants consisting of former UPK managers, local government officials, community groups, and academics, this study analyzes strategic communication and institutional transformation mechanisms through in-depth interviews, focus group discussions, participant observation, and document analysis. The findings indicate that effective organizational communication plays a critical role in managing the institutional transition. The UPK has substantial social capital, including 15 years of microfinance management experience, a network with 847 community groups, and local policy support. However, there are obstacles such as unclear technical regulations, limited human resources in the village, and resistance to change. A gradual transformation model is considered most feasible, utilizing a participatory communication approach that maintains stakeholder trust. This study concluded that the transformation of the UPK into the Merah Putih Village Cooperative shows high prospects if implemented gradually with an adaptive communication strategy and supported by clear regulations.